The politics of counter-reform in the Argentine pension system: Actors, political discourse, and policy performance - Arza, Camila (2012)
In November 2008, the Argentine National Congress passed a bill drafted by the executive branch to reform the country's pension system. The law eliminated the fully funded pension accounts created in 1993/94 and transferred all participants in that system to a pre-existing pay-as-you-go pension system. On the basis of debates in the National Congress and statements in the media, this article analyzes the political process of pension reform. It studies the positions of major actors and the arguments presented in favor of and against the bill. In sum, the article analyzes a recent policy experience that may be of interest to other countries in the region that have similar pension systems, offering empirical insights for conceptual analysis of institutional change and continuity.